Computational Estimation of Free Energy Using Fortran Code - Powrel, Jhulan (Butwal Campus Journal, 2022)
Theoretical physics based on several computational software. The code for theoretical calculations of free energy is essential in many of the software. One of the codes frequently used in molecular dynamics is FORTRAN (Formula Transformation) code. The free energy for thermal and conformational are found to be and respectively. The average of the total free energy of the theoretical system is found to be . The free energy of a system of theoretical molecule of butane is . The ranges of theoretical and experimental values of free energy are found to be in considerable range. So, the FORTRAN code can also be used in estimating the free energy of the system of molecules.